Sarcopenia as a Risk of Modern Obesity Treatments: A Review of Molecular Mechanisms and Prevention Strategies - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2025)
While lifestyle interventions and metabolic surgery for obesity have limitations, incretin-based therapies have emerged as highly effective treatments. However, their success is shadowed by a significant risk, which is the loss of lean skeletal muscle, which can induce sarcopenia or sarcopenic obesity. Given the vital role of skeletal muscle in overall health, it is crucial to accurately assess this condition using standard clinical measures. Exercise stands as the most potent countermeasure, acting as medicine to preserve muscle and improve metabolic health. Its benefits are driven by a complex interplay of mechanisms. Different exercise types trigger the release of myokines and exerkines, while a regulated inflammatory response is essential for muscle adaptation and regeneration. This regenerative process, involving muscle stem cells, is further governed by epigenetic factors and critical molecular pathways like Akt and insulin that maintain muscle mass. To optimize these effects, adequate protein intake and targeted nutritional strategies are essential, supporting muscle protein synthesis and recovery. Supplementation, particularly with leucine-rich amino acids or vitamin D, may further enhance anabolic responses, especially in older adults. Clinical monitoring of muscle mass, strength, and nutritional biomarkers should be integrated into obesity care to detect early signs of sarcopenia and guide individualized interventions. Therefore, it is imperative that obesity therapy evolves to prevent muscle loss. This review highlights the risk of therapy-induced sarcopenia from modern obesity treatments, emphasizing the need for integrated prevention strategies, centered on exercise, and reinforced by nutrition, supplementation, and clinical monitoring to ensure healthy, sustainable weight loss.KEYWORDS: sarcopenia, skeletal muscle, inflammation, obesity, incretin